The Mediating Role of Trust and its Relationship with the Perception of Convenience and Transparency on User Satisfaction of Electronic Procurement Services - Baskara, Abdullah; Nuryakin, Nuryakin; Handayani, Siti Dyah (Jurnal Manajerial, 2024)
Background – In the current 4.0 industrial revolution, the government is required to be able to create innovations including in public services based on information and communication technology. In addition, E-procurement is a form of innovation based on e-government which is almost entirely accomplished by making use of information and communication technology. Aim – This study aims to determine the effect of perceived convenience and transparency on Electronic Procurement Services or LPSE user trust, the effect of ease, transparency and trust on LPSE user satisfaction, the impact of trust in mediating the effect of perceived convenience on LPSE user satisfaction, and the role of trust in mediating the effect of transparency on LPSE user satisfaction. Design / Methodology / Approach – Respondents in this study were businessmen and consultants who had participated in tenders within the Ministry of Religion D. I. Yogyakarta as many as 180 respondents using the accidental sampling technique. A quantitative method of SEM and AMOS was applied in the study. Findings – From the tested and collected data, the results show that ease and transparency perceptions affect positively and significantly on user trust. Furthermore, the feeling of convenience, transparency and trust bring a favorable and significant impact on user satisfaction. User satisfaction is unaffected by user perception through trust as an intervening variable. Research implication – Transparency has no impact on customer satisfaction through trust as an intervening variable. Limitations – Further research taking independent variables other than perceptions of convenience, transparency and trust.